The Impact of Social Media Algorithms on Political Polarization and Public Discourse - Omar Farid (Global Journal of Multidisciplinary and Applied Sciences, 2025)
The proliferation of social media usage in Pakistan has coincided with growing concerns about political polarization and the reshaping of public discourse. This study examines how algorithmic curation by social media platforms affects exposure to political content, thereby influencing polarization and shaping public opinion. Using a mixed-methods approach — combining content analysis, user surveys, and echo chamber network mapping — this paper explores the relationship between algorithm-driven content personalization and the intensification of ideological divisions. The findings suggest that algorithms often amplify emotionally charged, partisan content, limiting exposure to diverse viewpoints and reinforcing echo chamber effects. The study concludes with recommendations for greater algorithmic transparency, media literacy, and regulatory oversight to foster more inclusive and balanced public discourse in digital spaces.